Implementing Activities Following the PPP Stages in a 10th Grade EFL Class to Foster Speaking Skill (2020)
ABSTRACT: This action research project aimed at exploring how the implementation of activities following the PPP stages can foster 10th graders speaking skill. To do this, students were exposed to speaking activities such as question charts, pronouncing tongue twisters, and class presentations that promoted oral participation while interacting and communicating with others using the target language. The data was gathered collecting students’ artifacts, class recordings, a focus group, and teacher’s journals. Analysis of data evidenced that learners were engaged when participating in speaking activities. Moreover, students’ self-confidence was found as an issue that helped them to improve their pronunciation. Besides, data showed that implementing tongue twisters in an English class helps students to improve their pronunciation.